Understanding barriers to housing delivery in informal settlements in Mariental, Namibia - Hungi, Kahorere Daryl (University of the Free State, 2020)
Housing is considered as one of the basic needs of a human being. In 1990, the government of the Republic of Namibia earmarked housing as a priority. Thus, the importance of effective and efficient housing delivery is crucial to the development of an urban area and the country at large. Apart from the value that formal housing adds to the lives of people through shelter and investment, housing is also an indicator of economic growth. Formal housing also creates sustainable communities and cities through poverty reduction. Despite the many initiatives employed by the Namibian government, housing the low-income groups remain a problem as in the case of Takarania Informal Settlement in Mariental, Namibia. Thus, policy makers need to understand the dynamics surrounding barriers which prevents low income groups in informal settlement from building formal houses. The support of both policy makers and implementers of housing delivery strategies is important for effective house delivery. This paper is intended to understand barriers to housing delivery in Takarania Informal Settlement in Mariental, Namibia. Triangulation of methods was used as semi-structured interviews, natural observation and structured questionnaires were used in gathering the needed information for the study. Interviews were planned to be conducted with at least 30 house owners, 3 staff members of the Mariental Municipality, 2 staff members of the Namibia Housing Action Group as well as one regional facilitator of the Shack Dwellers Federation of Namibia. Out of the targeted 30 house owners, 26 house owners participated in the research study. The findings suggest that there are multiple factors that serve as barriers to housing delivery in the Takarania Informal Settlement. Land tenure was found to be one of the main barriers to housing delivery. The lack of support for aided self-help as well as incremental housing options is another obstacle to housing delivery in Takarania. House owners in Takarania Informal Settlement finds it challenging to afford buying land and houses due to low monthly earnings and unemployment. Although the housing and town planning policy framework is articulated well, it does not seem to have been fully operationalised to address the housing needs of low-income groups such as Takarania residents. A major limitation of the study was the inability of the researcher to speak the native language of the region, which might have compromised the quality of the data collected.
Dissertation (MDS (Development Studies))--University of the Free State, 2020
Keywords: Informal settlements (Squatter settlements) - Namibia; Housing - Namibia